Surface mineral deposition and mechanical properties of one-step bonding agent with copper-modified niobium nanoparticles – An in vitro study - Obeid, Alyssa Teixeira; Velo, Marilia Mattar de Amoêdo Campos [UNESP]; de Lima Nascimento, Tatiana Rita; de Lucena, Fernanda Sandes; Guedes, Ana Paula de Melo Alves; Falcão Mendes, Ana Zélia; dos Santos, Adriana Nunes; Spironelli Ramos, Carlos Alberto; Mondelli, Rafael Francisco Lia; Soares Bombonatti, Juliana Fraga (Elsevier, 2024)
This study aimed to investigate the incorporation of copper-modified niobium (Nb/Cu) nanoparticles at concentrations of 0.1 % and 0.3 wt% in a one-step adhesive (PacBond Adhesive). Thirty sound human third molars were randomly divided into three groups: control, 0.1NbCu, and 0.3NbCu. Specimens were restored with PacBond and resin composite OptiComp, Composite LC. Stick specimens (0.64 mm2) were obtained and subjected to microtensile bond strength (MTBS) testing (n = 10) using a universal testing machine at a rate of 0.5 mm/min after 24 h and 6 months. Scanning electron microscope (SEM) analysis, microhardness after 24 h and immersion in ethanol (HK) (n = 7), degree of conversion (DC) (n = 6), and surface mineral deposition (n = 3) were also conducted. Data were analyzed using two-way ANOVA for MTBS and HK, and one-way ANOVA for %SHL and DC, all of them were followed by Tukey's test (p < 0.05). For MTBS, statistical difference in storage times was observed for 0.1NbCu after 24 h (p = 0.007). There was no statistical difference between the control and 0.3NbCu regarding time and materials after 24 h and 6 months (p = 0.065). There was no statistical difference among the groups for DC (p = 0.278), but there was a significant difference among the groups for the factor of time in HK measurements (p = 0.047). The 0.1NbCu and 0.3NbCu groups exhibited absorbance Bands indicative of surface mineral deposition after 14 and 21 days, and the 0.3NbCu interface showed better preservation in SEM analysis. The concentration of 0.3 % NbCu in a one-step adhesive appears promising and may offer enhanced longevity for the tooth/restoration interface.
Keywords: Copper; Dentin-bonding agents; Nanoparticles; Niobium